Pakistan’s Transport Sector Modeling Using AIM/Enduse - Waqas Nazir Awan; Sidra Khan; Muhammad Zulfiqar; Ubaid Ur Rehman Zia; Peng Wang (Engineering Proceedings)
Pakistan is actively exploring sustainable transportation solutions, considering environmental impact, and economic development. By adopting more sustainable modes of transport and investing in infrastructure, Pakistan can pave the way toward a greener and more efficient future. Leveraging the AIM/Enduse framework, we analyze the energy and environmental impact using Baseline (BL) and Counter Measure (CM) scenarios. Our findings indicate, with penetration of 30%, 50%, and 100% green vehicles into the existing transport system, Pakistan may save 5 MTOE, 11 MTOE, and 24.6 MTOE of energy in 2030, 2040, and 2050, respectively. Similarly, it will also reduce CO2 emissions by 22 MtCO2eq, 41 MtCO2eq, and 104 MtCO2eq in respective years.